2017
DOI: 10.1111/jmwh.12658
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Body, Mind, and Environment in Preterm Birth: Mind the Gap

Abstract: Preterm birth continues to be a problem affecting low-, middle-, and high-income countries, with rates increasing in some areas despite ongoing efforts to reduce the incidence. This emphasizes the need for more effective interventions, particularly if we aim to achieve the broad health targets of the Sustainable Development Goals (SDGs) by 2030. The current focus on medically-oriented interventions such as reducing nonmedically-indicated induction of labor, cesarean birth, and multiple embryo transfers associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 88 publications
(296 reference statements)
0
5
0
Order By: Relevance
“…One previous study examined paternal cancer history in relation to birth outcomes and did not observe a significantly elevated risk of PTB among offspring of male survivors with CNS tumor (RR = 1.31, 95% CI = 0.55–3.12), but the result should be interpreted with caution due to a small sample size ( n = 47) . Both physiological and psychological factors may potentially lead to a higher risk of PTB, including hormonal alterations, reproductive organ damage and prenatal depression or anxiety . A number of studies have indicated that survivors with CNS tumor suffered an elevated risk of depression, anxiety and other psychological problems, which was suggested to be associated with subsequent higher risk of PTB, in particular among female survivors .…”
Section: Discussionmentioning
confidence: 93%
“…One previous study examined paternal cancer history in relation to birth outcomes and did not observe a significantly elevated risk of PTB among offspring of male survivors with CNS tumor (RR = 1.31, 95% CI = 0.55–3.12), but the result should be interpreted with caution due to a small sample size ( n = 47) . Both physiological and psychological factors may potentially lead to a higher risk of PTB, including hormonal alterations, reproductive organ damage and prenatal depression or anxiety . A number of studies have indicated that survivors with CNS tumor suffered an elevated risk of depression, anxiety and other psychological problems, which was suggested to be associated with subsequent higher risk of PTB, in particular among female survivors .…”
Section: Discussionmentioning
confidence: 93%
“…Because in prior studies housing status has been associated with sociodemographic 26 and health factors 26 and access to care, 11 we included the following covariates for matching based on their previously reported associations with PTB: race/ethnicity, 4 maternal age, 4 parity, 27 prior PTB, 4 body mass index, 4,28 tobacco use during pregnancy, 4 alcohol 4,27 or drug abuse during pregnancy, 27 maternal hypertension, 27 maternal diabetes, 27 mental health conditions during pregnancy, 5,29,30 adequacy of prenatal care (using the Adequacy of Prenatal Care Utilization Index), 31,32 and maternal education. 27 We additionally matched on type of neonatal intensive care unit at the birth hospital.…”
Section: Covariatesmentioning
confidence: 99%
“…[15] Given the interactive nature of nutrition, physical health, and mental health for pregnant women, it is imperative to consider these factors in tandem when predicting birth outcomes. [16] Models that include sociodemographic, food insecurity, physical health, mental health, and substance use predictors of birth outcomes are needed to disentangle impacts on birth outcomes and to guide intervention efforts to improve maternal and infant health in LMICs. [17] The aim of this study was to comprehensively investigate maternal physical and mental health during pregnancy and the impact on birth outcomes in a South African birth cohort study, the Drakenstein Child Health Study (DCHS).…”
Section: Introductionmentioning
confidence: 99%